2022
DOI: 10.1002/aenm.202103045
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Substitution in Ni‐Rich NMC Layered Cathodes for High‐Energy Lithium Ion Batteries

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/aenm.202103045.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 81 publications
0
57
1
Order By: Relevance
“…There is a continuing demand from the end user for lithium-ion batteries to have higher energy density, be safer, and be lower in cost. The cathode is one major challenge to address these needs. , Among the cathode materials, the layered transition metal oxide materials, starting with the original LiCoO 2 , are the most studied and used. , Of these, the Ni-rich cathode materials, commonly described as NMCA, LiNi 1– z – y – q Mn z Co y Al q O 2 , have the highest energy density and technological maturity. However, to reduce cost, the cobalt content must be reduced as much as possible, and to increase electrochemical capacity, the nickel content needs to be increased. Batteries containing 60% nickel are now readily available commercially, and 80% nickel is becoming more readily available. However, beginning around 80% nickel the synthesis process becomes more complicated, requiring a pure oxygen environment during reaction. , Some of the other issues are high reactivity toward moisture due to Li residual impurities, , enhanced cation mixing, surface phase transitions from layered to spinel and rock-salt structures, dissolution of transition metal to incessant electrolyte consumption, , intergranular microcracking formation in secondary particles upon cycling, resulting in interfacial resistance, , and reactivity issues due to the lower thermal stability of the charged electrode. , These issues are the key challenges in NMCs’ commercialization with Ni content ≥80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a continuing demand from the end user for lithium-ion batteries to have higher energy density, be safer, and be lower in cost. The cathode is one major challenge to address these needs. , Among the cathode materials, the layered transition metal oxide materials, starting with the original LiCoO 2 , are the most studied and used. , Of these, the Ni-rich cathode materials, commonly described as NMCA, LiNi 1– z – y – q Mn z Co y Al q O 2 , have the highest energy density and technological maturity. However, to reduce cost, the cobalt content must be reduced as much as possible, and to increase electrochemical capacity, the nickel content needs to be increased. Batteries containing 60% nickel are now readily available commercially, and 80% nickel is becoming more readily available. However, beginning around 80% nickel the synthesis process becomes more complicated, requiring a pure oxygen environment during reaction. , Some of the other issues are high reactivity toward moisture due to Li residual impurities, , enhanced cation mixing, surface phase transitions from layered to spinel and rock-salt structures, dissolution of transition metal to incessant electrolyte consumption, , intergranular microcracking formation in secondary particles upon cycling, resulting in interfacial resistance, , and reactivity issues due to the lower thermal stability of the charged electrode. , These issues are the key challenges in NMCs’ commercialization with Ni content ≥80%.…”
Section: Introductionmentioning
confidence: 99%
“…A common strategy to reduce the degradation of the cathode material and to enhance its electrochemical performance is to modify the surface by a coating and/or the bulk by partial elemental substitution. ,, Surface modification reduces the reactivity of the oxide with the electrolyte and may at the same time lower the possible dissolution of transition metal ions. All these layered oxides are also thermodynamically unstable on removal of the lithium ions and have a tendency to lose oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…When matched with a graphite anode, Mg‐doped LiNi 0.9 Co 0.05 Mn 0.05 O 2 (NCM900505) showed better cycling performance than pristine NCM900505 (Figure 7D). [ 81 ] In addition, the doping of Mg 2+ is also found to shift the onset of the exothermic reaction and phase transition toward higher temperature, improving the thermal stability of the NCM cathode (Figure 7E).…”
Section: Ionic Dopingmentioning
confidence: 99%
“…Recently, element doping has also been widely used to control the internal microstructure of secondary particles, interface structure of the particle surface and primary particle size of cathode materials to optimize electrochemical properties. The commonly used cation doping elements for Ni-rich cathode materials are Na, Mg, Ca, B, Al, Ti, Zr and so on [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Some cation dopants can be incorporated into the crystal lattice interlayers of Ni-rich cathode materials as “pillar ions” to stabilize the bulk structure.…”
Section: Modificationsmentioning
confidence: 99%
“…Schmuch et al [ 69 ] indicated that 2 mol % Mg-doped cathode material possessed superior electrochemical properties. Its key electrochemical performance index is equivalent to that of commercial NCM811 material, and it has the additional advantage of reducing the Co content as a key raw material.…”
Section: Modificationsmentioning
confidence: 99%